Pluronic® L64-mediated stable HIF-1α expression in muscle for therapeutic angiogenesis in mouse hindlimb ischemia - Song H (Dove Medical Press, 2014)
Hongmei Song,1 Sijia Liu,1 Caixia Li,1,2 Yanyan Geng,1,3 Gang Wang,1 Zhongwei Gu1 1National Engineering Research Center for Biomaterials, Sichuan University, Chengdu, People’s Republic of China; 2Chengdu Institute of Biology, Chinese Academy of Sciences, Chengdu, People’s Republic of China; 3Hebei University of Engineering, Handan, Hebei, People’s Republic of China Abstract: Intramuscular injection of plasmid DNA (pDNA) to express a therapeutic protein is a promising method for the treatment of many diseases. However, the therapeutic applications are usually hindered by gene delivery efficiency and expression level. In this study, critical factors in a pDNA-based gene therapy system, such as gene delivery materials, a therapeutic gene, and its regulatory elements, were optimized to establish an integrated system for the treatment of mouse hindlimb ischemia. The results showed that Pluronic® L64 (L64) was an efficient and safe material for gene delivery into mouse skeletal muscle. It also showed intrinsic ability to promote in vivo angiogenesis in a concentration-dependent manner, which might be through the activation of nuclear factor kappa-light-chain-enhancer of activated B cell (NF-κB)-regulated angiogenic factors. The combination of 0.1% L64 with a hybrid gene promoter (pSC) increased the gene expression level, elongated the gene expression duration, and enhanced the number of transfected muscle fibers. In mice ischemic limbs, a gene medicine (pSC-HIF1αtri/L64) composed of L64 and pSC-based expression plasmid encoding hypoxia-inducible factor 1-alpha triple mutant (HIF-1αtri), improved the expression of stable HIF-1α, and in turn, the expression of multiple angiogenic factors. As a result, the ischemic limbs showed accelerated function recovery, reduced foot necrosis, faster blood reperfusion, and higher capillary density. These results indicated that the pSC-HIF1αtri/L64 combination presented a potential and convenient venue for the treatment of peripheral vascular diseases, especially critical limb ischemia. Keywords: gene therapy, Pluronic L64, angiogenesis, SV40 enhancer, HIF-1α